2007
DOI: 10.1073/pnas.0700163104
|View full text |Cite
|
Sign up to set email alerts
|

The GABA A receptor α1 subunit epilepsy mutation A322D inhibits transmembrane helix formation and causes proteasomal degradation

Abstract: A form of autosomal dominant juvenile myoclonic epilepsy is caused by a nonconservative missense mutation, A322D, in the GABA A receptor ␣1 subunit M3 transmembrane helix. We reported previously that the A322D mutation reduced total and surface ␣1(A322D) subunit protein and that residual ␣1(A322D) subunit resided in the endoplasmic reticulum. Here, we demonstrate that the reduction in ␣1(A322D) expression results from rapid endoplasmic reticulum-associated degradation of the ␣1(A322D) subunit through the ubiqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 38 publications
7
82
0
1
Order By: Relevance
“…Therefore, these experiments provide compelling evidence that the lysosomal targeting of GABA A Rs depends on the ubiquitination of lysine residues between residues 317-338 of the ␥2 subunit. Ubiquitination of lysine residues within the intracellular loops of the GABA A R ␣1 and ␤3 subunits can target unassembled subunits within the endoplasmic reticulum (ER) for ER associated degradation by the proteosome, but does not appear to be involved in GABA A R endocytic trafficking (17,18). Moreover, this proteosomal degradation of GABA A R subunits within the secretory pathway regulates synaptic inhibition over long time scales (days) (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these experiments provide compelling evidence that the lysosomal targeting of GABA A Rs depends on the ubiquitination of lysine residues between residues 317-338 of the ␥2 subunit. Ubiquitination of lysine residues within the intracellular loops of the GABA A R ␣1 and ␤3 subunits can target unassembled subunits within the endoplasmic reticulum (ER) for ER associated degradation by the proteosome, but does not appear to be involved in GABA A R endocytic trafficking (17,18). Moreover, this proteosomal degradation of GABA A R subunits within the secretory pathway regulates synaptic inhibition over long time scales (days) (17).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies on the role of ubiquitination in regulating synaptic function under normal conditions and in pathological conditions such as ischemia have focused on the ubiquitin-proteasome system (14)(15)(16)(17)(18). However, within the endocytic pathway, mono-ubiquitination (or the addition of short ubiquitin chains) is a key signal that results in the specific targeting of cargo to late endosomes for subsequent lysosomal degradation (12,19,20).…”
mentioning
confidence: 99%
“…The ␣1(A322D) subunits cannot efficiently form the TM3 ␣ helix in the ER membrane, resulting in its misfolding (40). Misfolded ␣1(A322D) subunits are recognized by the ER quality control machinery, polyubiquitinated, extracted from the ER membrane to the cytosol, and targeted to the proteasome for degradation.…”
Section: Discussionmentioning
confidence: 99%
“…35 S]methionine chase result (39,40). EerI treatment (5 M, 6 h) increased the half-life of the ␣1(A322D) subunit from 45 to 82 min, and, remarkably, coapplication of SAHA (2.5 M, 24 h) further extended its half-life to 130 min (Fig.…”
Section: Inhibiting Vcp Using Eeyarestatin I Increases the Total Protmentioning
confidence: 99%
“…In addition, the study by Sanders and Myers (2004) revealed that many diseaselinked mutations result from loss of protein function and from protein misfolding, which alters protein function, assembly, or subcellular trafficking, but not protein topology. Gallagher et al (2007) showed that the GABA A R α 1 epilepsy mutation A322D reduced total α 1 (A322D) subunit expression, altered α 1 subunit topology, inhibited transmembrane helix formation, and caused proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%